The Effect of Workload and Work Stress on Officers’ Performance and Job Satisfaction as Intervening Variable in Municipal Police Unit, East Borneo Province - Dony Muslim; Zainal Ilmi; Irwansyah Irwansyah (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to investigate the effect of workload and work stress on job performance and job satisfaction as intervening variable in Municipal Police Unit, East Borneo Province. The purpose of this study is to explain the position and relationship between the variables measured as well as to do hypothesis testing in the study. The research design uses explanative research with a quantitative approach. The population in this study is 69 officers in Municipal Police Unit, East Borneo Province. All of the population is taken as samples in this study. the data is gathered from distributing questionnaires to 69 samples in this study. The finding shows that there is a negative and significant effect of workload on job satisfaction. It also found that there is a negative and significant influence of work stress on job satisfaction. The result also indicates that there is a positive and significant effect of job satisfaction on job performance. It is also found that there is a negative and significant influence of workload on job performance. The result also indicates that there is a negative and significant influence of work stress on job performance. Furthermore, there is a mediating effect of job satisfaction between workload on job performance. It is also found that there is a mediating effect of job satisfaction between work stress on job performance.